Protective Effects of One 2,4-Dihydro-3H-Pyrazol-3-one Derivative against Posterior Capsular Opacification by Regulation of TGF-β2/SMADs and Non-SMAD Signaling, Collagen I, and Fibronectin Proteins - Chun-Ching Shih; Chia-Yi Lee; Fung-Fuh Wong; Cheng-Hsiu Lin (Current Issues in Molecular Biology, 2022)
Many elderly individuals frequently experience cataracts that interfere with vision. After cataract surgery, the left lens epithelial cell (LEC) exhibited fibrosis and posterior capsule opacification (PCO). Sometimes, there is a need for a second surgery; nevertheless, people try other methods, such as a good pharmacological agent, to treat PCO to reduce transforming growth factor-β2 (TGF-β2) amounts to avoid secondary surgery. The aim of the present study was to explore the potential anti-PCO activity of five 2,4-dihydro-3H-pyrazol-3-one (DHPO) derivatives in a TGF-β2-induced fibrogenesis SRA01/04 cell model. The 2-phenyl-5-propyl-DHPO (TSE; no. 2: TSE-2) compound showed the best activity of reduced expression levels of TGF-β2 among five derivatives and therefore was chosen to evaluate the anti-PCO activity and molecular mechanisms on the Sma and mad protein (SMAD) signaling pathway (including TGF-β2, SMADs, and the inhibition of nuclear translocation of SMADs), non-SMAD pathway proteins, including p-extracellular, regulated protein kinases (ERK) 1/2, or p-c-Jun N-terminal kinase (JUN) by Western blotting, PCR, or confocal immunofluorescence analyses. Following treatment with 10 μg/mL of the five compounds, the cells displayed great viability by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTT) assay. In this study, the result of lactate dehydrogenase (LDH) activity measurement did not affect the cytotoxicity of the five compounds. In TGF-β2-induced fibrogenesis in SRA01/04 cells, treatment with the TSE compound decreased the TGF-β2/SMAD signaling genes, including reduced mRNA or expression levels of TGF-β2, SMAD3, and SMAD4, leading to inhibition of TGF-β2-induced fibrogenesis. Our confocal immunofluorescence analyses demonstrated that TSE treatment displays a suppressive effect on SMAD2/3 or SMAD4 translocation to the nucleus. Furthermore, TSE treatment exhibits a reduction in the non-SMAD target gene expression levels of p- c-Jun N-terminal kinase (JUN), p- extracellular, regulated protein kinases (ERK)1/2, p- p38 mitogen-activated protein kinase (p38), p-phosphatidylinositol 3-kinase (PI3K), p-mammalian target of rapamycin complex (mTORC), p-Akt (Ser473), and p-Akt (Thr308). The overall effect of TSE is to reduce the expression levels of collagen I and fibrinogen (FN), thus contributing to antifibrotic effects in cell models mimicking PCO. Our findings reveal the benefits of TSE by regulating TGF-β/SMAD signaling and non-SMAD signaling-related gene proteins to display antifibrotic activity in cells for the possibility of preventing PCO after cataract surgery.